Modified Kuppuswamy socioeconomic scale: 2022 update of India - Sood, Parul; Bindra, Supreet (International Journal Of Community Medicine And Public Health, 2022)
The term "socioeconomic status" (SES) refers to a measurement that takes into account a family’s income, level of education, and the occupation of the family’s primary breadwinner. This helps to evaluate the family overall health as well as their access to resources. Kuppuswamy SES is one of the commonest scales used to determine SES of people residing in urban areas, but it requires updating because of steady inflation in the value of rupees based on change in consumer price index. The updated version of modified Kuppuswamy socioeconomic scale for the year 2022 in India is thus presented.